A country strange and far: the Methodist Church in the Pacific Northwest, 1834-1918 - McKenzie, Michael C. (University of Nebraska Press, 2022)
Machine generated contents note: List of Illustrations -- Acknowledgements -- Prologue: Listening to Janus -- Introduction: Death of the Old Gods -- -- PART ONE: IMMIGRANT RESISTANCE -- Chapter 1: A Man Overwhelmed -- Chapter 2: Broken is the Tie that Binds -- -- PART TWO: NATIVE RESISTANCE -- Chapter 3: Miracle in the Valley? -- -- PART THREE: URBAN RESISTANCE -- Chapter 4: A "Damned Hilly Place" -- Chapter 5: The Peopled Cities -- -- PART FOUR: ARID RESISTANCE -- Chapter 6: Dry and Scattered -- -- PART FIVE: INNER RESISTANCE -- Chapter 7: As the Lion Lay Dying -- -- Epilogue: Just a Few Bones -- Notes -- Bibliography -- Index -- .